Protection of human capital against depreciation as the primary reason for providing compensation - Oliwkiewicz, Barbara (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The family is the only supplier of human capital to the labour market. A prerequisite for maintaining a proper level of human capital in the household is to provide the employee with a fair wage. A good wage is one that gives the opportunity to reproduce human capital at least on the same level, both in the short and long term. The growth and method of paying human capital is one of the main economic processes taking place in the household. Human capital has a unique character that is characterized by inalienability. The capital is individual and assigned to a specific holder of human capital. However, inalienable does not apply to the long period of generational exchange. Man, as the owner of capital, prepares his successors (children) to provide work and functioning in society. However, a reasonable remuneration does not guarantee full reconstruction of human capital. Families may be guided by various preferences when it comes to using their income at their disposal. Reasonable and creative actions of family members will lead to an additional increase in human capital. However, the lack of care for health or the use of available resources in a careless manner, e.g. alcohol abuse will lower its value. The purpose of this article is to present the role of the family in shaping human capital as well as an attempt to estimate the minimum fair remuneration in Poland, which will enable the reconstruction of human capital in the short and long-term through generational exchange.

Rodzina jest jedynym dostawcą kapitału ludzkiego na rynek pracy. Warunkiem koniecznym utrzymania odpowiedniego poziomu kapitału ludzkiego w gospodarstwie domowym jest zapewnienie pracownikowi płacy godziwej. Godziwa płaca to taka, która daje możliwość odtworzenia kapitału ludzkiego przynajmniej na tym samym poziomie zarówno w krótkim, jak i w długim okresie. Wzrost i sposób opłacania kapitału ludzkiego to jeden z głównych procesów ekonomicznych mających miejsce w gospodarstwie domowym. Kapitał ludzki ma unikalny charakter, który cechuje się niezbywalnością. Kapitał jest indywidualny i przypisany do konkretnego posiadacza kapitału ludzkiego. Jednakże niezbywalność nie dotyczy długiego okresu, jakim jest wymiana pokoleń. Człowiek, jako posiadacz kapitału, prowadzi przygotowania swoich następców (dzieci) do świadczenia pracy i funkcjonowania w społeczeństwie. Godziwe wynagrodzenie jednak nie gwarantuje pełnego odtworzenia kapitału ludzkiego. Rodziny mogą się kierować różnymi preferencjami, jeśli chodzi o wykorzystanie dochodu pozostającego w ich dyspozycji. Rozsądne i twórcze działania członków rodziny doprowadzą do dodatkowego wzrostu kapitału ludzkiego. Natomiast brak troski o zdrowie lub wykorzystywanie dostępny środków w niefrasobliwy sposób, np. nadużywanie alkoholu, spowodują obniżenie jego wartości. Celem niniejszego artykułu jest przedstawienie roli rodziny w kształtowaniu kapitału ludzkiego, jak również próba oszacowania minimalnego wynagrodzenia godziwego w Polsce, które umożliwi odtworzenie kapitału ludzkiego w krótkim i w długim okresie poprzez wymianę pokoleniową.
Keywords: minimum wage; human capital; fair remuneration; work; płaca minimalna; kapitał ludzki; wynagrodzenie godziwe; praca